Effect of Stocking Density, Feed Type and Feeding Time on Growth and Survival Rate of Whiteleg Prawn (Penaeus vannamei) - Farida, Farida; Masyahoro, Abdul; Rusaini, Rusaini (FAPETKAN UNTAD, 2019)
The objective of the research was to determine the effect of stocking density, feed type and feeding time on the growth and survival rate of juvenile whiteleg prawn (Penaeus vannamei) cultured in an extensive pond. A completely randomized design (CRD) was applied to a split-split plot design with three factor (stocking density as primary factor, feed type as sub-factor, and feeding time as sub-sub factor), giving 8 treatment combinations with 3 replicates (24 experimental units). Analysis of variance did not indicate any significant interaction between the effects of treatments on whiteleg prawn growth of any two or three factors (P > 0.05). Both stocking density (5 or 10 prawns/m3) and feed type (snails or corn) had a significant effect (P <0.05) on growth, while the effect of feeding time (day or night) was not significant (P > 0.05). Absolute growth of juvenile whiteleg prawn ranged from 2.16 to 7.03 g/prawn with a survival rate range of 60-100%.Keyword: whiteleg prawn, stocking density, feed type and feeding time.